Names to describe achromatic colors in Proto-Slavic language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Research the history of the vocabulary of the Ukrainian language is impossible without elucidation of Certain semantic groups of vocabulary, including koloratyviv. In the article the name achromatic colors in Proto-Slavic language. According to sources recorded koloroleksemy white, black, gray, and their derivatives. Proto-Slavic language, vyokremyvshys of Indo-European, inherited the basic color term. Fore-slavic formed on the basis of token Indo-European roots by using the word-building tools inherited from Indo-European languages and Emerging in Proto-Slavic language. Early examples of character, spreading in the Slavic languages suggest prescription derived from the base *bĕlъ. The word white in the semantic evolution changes the value to etymological derivative (metaphorical), based on his creation is the effect of visual perception (sema “Lights”). In the Common era adjective meant the color name for such a value is used in all modern Slavic languages. Conventionally, the ego can be considered Pervin (despite metaforichnist ego origin), the chronological framework of the study the initial stages of World Health Report Common (or Slavonic) period. With roots in antiquity protein complex fixed low prikmetnikiv Slavonic type. Derivative imenniki existed, verb, adjective of color from black, matching complex derivatives. From the root *si-/*sei- convulsive formation later shryi adjective, verb like shine “blyskuchiyi shining”. Of Slavonic form came koloronomen gray. Color term in Old Church Slavonic monuments reflect later Slavonic period. Analyzed a number of sources confirm the names of koloronomeniv derivatives, complex derivatives.
Keywords: color term; token white; black; gray; koloratyv derived words; abstract tokens